A Study on Japanese Language Learning Anxiety and Self regulation among Japanese Language Majors - Ping, Jing (Journal of Theory and Practice of Social Science, 2024)
In recent years, with the rapid development of urban economy and the continuous improvement of motorization level, serious environmental pollution problems and increasing traffic pressure are not conducive to the sustainable development of cities. The launch of shared bicycles can take advantage of the convenience and privileges when renting in connection, etc., attract more those to choose public transportation, so as to improve the urban traffic environment and accelerate the sustainable development of the cities. Ten departments including the Ministry of Transport jointly announced the "Guideline on Encouraging and Regulating the Development of Internet Rental Bicycles", it defined that shared bicycle is an important part of the urban green transportation system and implemented policies to encourage development. With the development of global economic integration and the increasingly frequent international exchanges and cooperation, foreign language learning has become more and more popular among college students. With the increasing number of Students majoring in Japanese, attention should be paid to the anxiety in learning Japanese. Based on this, this paper firstly analyzes the causes of Japanese learning anxiety of Japanese major students and puts forward self-adjustment methods.